IMPLEMENTASI KEBIJAKAN PENERTIBAN HEWAN TERNAK DI KABUPATEN PARIGI MOUTONG - Otoluwa, Windi Handayani (Katalogis, 2017)
This study aims to determine the Implementation of animal control policy at Parigi Moutong regency. Furthermore, this study using the Theory of Van Meter and Van Horn with basic descriptive type and qualitative research. In this study, the selection of informants was taken purposively. Where researchers deliberately would choose those that are considered to understand the issues examined. Data was collected through observation, interviews, and documentation. Based on the results of the study showed that the Implementation of animal control policy at Parigi Moutong regency has not gone well given the weakness of the sanction given to farmers who let their animals roam the bodies roads, and lack of traction on the implementor in this case the relevant institutions in implementing regulations No. 25 of 2005 on the Control of livestock and there are still farmers/herders are indifferent or less aware of the impact arising from their livestock if released or roam in any place.